Social Norms and Entrepreneurial Intention in University Researchers in Colombia - Tarapuez Chamorro, Edwin; Parra-Hernández, Ramiro; Gil-Giraldo, Alejandra (Cuadernos de Administración, 2020)
Social or subjective norms (SN) can be defined as the guidelines that seek to shape the behavior of people within society based on the different beliefs and customs of the distinct groups that comprise it. Usually, SN are not written, but are known by people. Entrepreneurial intention (EI), on the other hand, is a previous step to the creation of a company that does not always take shape in the assembly of new businesses. The objectives of this work were to find associations between the SN and the other variables analyzed, and to identify the SN that determine EI among university researchers in Colombia. The research is descriptive and correlational, and has a non-experimental and cross-sectional design. A stratified random sample is taken from peer evaluators from the Colombian Administrative Department of Science, Technology, and Innovation (COLCIENCIAS) in the areas of science, technology, engineering, and mathematics. The results show that SN do determine the EI of university researchers and that these are related to guidelines that shape their behavior in three ways: a) the positive image of the entrepreneur from values, such as their dedication to work and their autonomy; b) social motivation to become an entrepreneur instead of being employed; and c) admiration for the entrepreneur and money as secondary elements that motivate EI.